Cover. (25th October 2018) - Gomez‐Lopez, Nardhy; Romero, Roberto; Panaitescu, Bogdan; Leng, Yaozhu; Xu, Yi; Tarca, Adi L.; Faro, Jonathan; Pacora, Percy; Hassan, Sonia S.; Hsu, Chaur‐Dong
Abstract : The cover image is based on the Original Article Inflammasome activation during spontaneous preterm labor with intra‐amniotic infection or sterile intra‐amniotic inflammation, by Nardhy Gomez‐Lopez et al., DOI10.1111/aji.13049 .